صراع الهيمنة بين الولايات المتحدة الأمريكية والصين في الفضاء السيبراني: دراسة جيوبوليتيكية في الاستراتيجيات والمآلات - دحماني سليم (Universty Of El-oued جامعة الوادي, 2024)
الملخص: لطالما كان الفضاء السيبراني (الأنترنيت) مشروعاً أمريكياً، قادت الولايات المتحدة تطوره منذ بدايته كمشروع لربط جهازي كمبيوتر في وزارة الدفاع إلى أن أصبح أكبر منصة استراتيجية عالمية تربط أكثر من ثلثي سكان العالم تتحكم في تواصلهم وآرائهم، تُشكل اقتصادهم وأمنهم، ومع ذلك، فإن هذه الميزات التي كانت تتدفق على واشنطن بدأت في تغيير وجهتها نحو بكين، ذلك أن صعود الصين التكنولوجي في العقد الثاني من الألفية الثالثة هدد الريادة الأمريكية وخلق تحدياً حقيقياً لقيادتها، فالصين وتحت حكم الرئيس "شي" لديها خطط كبرى لتحويل الصين إلى "قوة سيبرانية عظمى" و"دولة ذكية" كنموذج لقيادة العالم. وعليه، تبيّن لنا من خلال تطبيق المقاربات الجيوبولتيكية التي أثبتت ملاءمتها وقدرتها في تفسير تجليات الصراع بين الولايات المتحدة والصين في الفضاء السيبراني عبر كل طبقاته، أن كلا القوتين تنطلقان من رؤيتهما الجيوبولتيكية وإدراكهما الاستراتيجي للفضاء السيبراني في تطوير وبناء استراتيجيات لإدارة هذا الصراع. فالولايات المتحدة تهدف استراتيجياتها المتعددة لزيادة النفوذ والسيطرة على الفضاء السيبراني وتحقيق والحفاظ على وضع الهيمنة مع احتواء وتقييد للصعود التكنولوجي الصيني، ومن جهتها الصين تسعى من خلال استراتيجياتها للصمود وجعل الصين مركزاً رائداً للتكنولوجيا، تنطلق من خلاله نحو العالم. كما تم التوصل إلى أن جيوبوليتيكا صناعة الرقائق تتحكم في مستقبل الصراع، فعلى المدى القريب يستمر الصراع في شكل حرب باردة رقمية، وعلى المديين المتوسط والبعيد يتأرجح بين ضبط للصراع واستقرار للفضاء السيبراني، وبين هيمنة طرف وفرض رؤيته على الطرف الآخر وعلى العالم، تفكك الفضاء السيبراني، أو حدوث حرب سيبرانية تدمر الفضاء السيبراني في أسوء الاحتمالات. Abstract: Cyberspace (Internet) has always been an American project. The United States led its development from its beginning as a project to connect two DoD’s computers until it became the largest strategic platform in the world,this platform connects more than two-thirds of the world’s population, controls their communication, opinions, shapes their economy and security. However, Cyberspace advantages that were flowing to Washington began to change direction towards Beijing. Wherefore, the technological riseof China in the second decade of the third millennium threatened US leadership and created a real challenge. Under the rule of President Xi, China has major plans to transform China into a “super cyberpower.” And make a “smart country” as a world leadership model. Accordingly, the application of geopolitical approaches has proven their suitability and ability to explain the US-China conflict in cyberspace across all its layers, it has become clear to us that both powers are starting from their geopolitical vision and strategic awareness of cyberspace to develop and buildtheir Conflict Management Strategies. In one hand, the US strategies aims to increase their influence and control over cyberspace, achieve and maintain a hegemonic position, while containing and restricting the Chinese technological rise. In the Other hand, China seeks, through its strategies, to remain steadfast and make China a leading center for technology, through which it will move towards the world. At the end, we concluded that the Semiconductors geopolitics controls the future of the US-China conflict in Cyberspace. In short term, this conflict continues in the form ofCyberCold War. However, in the medium/long term, it fluctuates between, firstly, controlling the conflict and stabilizing cyberspace, secondly, the dominance of one power and imposing its vision on the other powers and on theentire world, thirdly, the disintegration of Cyberspace. finaly,a cyber war destroysthe Cyberspace in the worst scenario.
أطروحة دكتوراه
Keywords: التنافس الامريكي الصيني; الجيوبوليتيك; الرقائق; الهيمنة الرقمية; الحرب البادرة الرقمية; US-China Conflict; Geopolitics; Semiconductors; Cyber Hegemony; Cyber Cold War